1993
DOI: 10.1177/107110079301400204
|View full text |Cite
|
Sign up to set email alerts
|

American Orthopaedic Foot and Ankle Society Women's Shoe Survey

Abstract: Shoes have been implicated as being responsible for the majority of foot deformities and problems that physicians encounter in women. A total of 356 women were studied in this investigation to evaluate trends in women's shoe wear and their effect on the development of foot deformities and pain. The majority of women in this study wore shoes that were too small for their feet, had foot pain and deformity, and had increased shoe size since the age of 20. Few women had their feet measured in over 5 years. The wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
106
0
9

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(117 citation statements)
references
References 6 publications
2
106
0
9
Order By: Relevance
“…However, the opportunity to perform daily activities such as stair descent while barefoot is rare. In addition, modern shoes, usually heel elevated with a rigid sole, are commonly used by the majority of women in their everyday lives (11). There is evidence that these types of shoes generate higher knee torques during locomotion when compared to barefoot locomotion (12), and because of their lower malleability, modern shoes can damage knee joints with OA, as they do not reproduce the flexibility of the movements of the foot when it is bare or that of the lower extremity as a whole (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, the opportunity to perform daily activities such as stair descent while barefoot is rare. In addition, modern shoes, usually heel elevated with a rigid sole, are commonly used by the majority of women in their everyday lives (11). There is evidence that these types of shoes generate higher knee torques during locomotion when compared to barefoot locomotion (12), and because of their lower malleability, modern shoes can damage knee joints with OA, as they do not reproduce the flexibility of the movements of the foot when it is bare or that of the lower extremity as a whole (8).…”
Section: Introductionmentioning
confidence: 99%
“…Women wear shoes with different heel heights and many women prefer to wear high-heeled shoes on a daily basis 1) . Older women who wear high-heeled shoes have an 83% prevalence of foot problems and usually have more foot problems than younger women 2) .…”
Section: Introductionmentioning
confidence: 99%
“…To this statistic, data can be added regarding the number of people with rheumatism, people with congenital deformities, people with amputations. Thus, in a study conducted in 1993, a total of 356 female subjects with normal feet, aged 20-60, were evaluated in the U.S. on the effects of wearing unsuitable footwear in terms of dimension [12]. The results of the study revealed that approximately 80% reported pain particularly in the toes (58%) and/or the instep (27%).…”
Section: Introductionmentioning
confidence: 99%
“…La aceastã statisticã se pot adãuga date despre numãrul persoanelor cu reumatism, persoane cu deformaþii congenitale, persoane cu amputaþii. Astfel, într-un studiu efectuat în anul 1993, un numãr de 356 subiecþi de sex feminin cu picior normal, cu vârstã între 20 ºi 60 de ani, au fost evaluaþi în SUA cu privire la efectele purtãrii încãlþãmintei inadecvate sub aspect dimensional [12]. Rezultatele studiului au relevat faptul cã aproximativ 80% au raportat durere în special în zona degetelor (58%) ºi/sau în zona ristului (27%).…”
Section: Introductionunclassified